Effects of Blood and Plasma Transfusion on Various Haematological and Biochemical Parameters In Anaemic Calves - Tamanna, Nafisa Yeasmin; Saha, Mousumi; Runa, Rukhsana Amin; Alam, Md Rafiqul (Research in Agriculture Livestock and Fisheries, 2022)
This experiment was performed to investigate the effects of blood and plasma transfusion on various haematological and biochemical parameters in anaemic calves. Ten apparently malnourished, anaemic calves were selected and divided into two equal groups. Group-A (n = 5) received blood and Group-B received plasma. The pre and post transfusion haematological and biochemical parameters recorded include total erythrocyte count (TEC), total leucocyte count (TLC), haemoglobin (Hb), packed cell volume (PCV), differential leukocyte count (DLC), Creatinine, ALT, AST and serum electrolytes ( K+, Na+, Cl-) at day 1, 7, 14, 21 and 28. The post transfusion values of TEC, PCV and Hb increased significantly (P< 0.01) in both the groups. However, the values were superior in case of blood transfusion. The changes in TLC and DLC values in both the groups A and B were not significant during the experiment. The mean control values of Creatinine, ALT and AST were found to be increased up to day 14 in calves of both group A and B. However, the changes in these biochemical parameters were not statistically significant and the values remained within the normal range. The changes in the values of the serum electrolytes did not follow any definite pattern during the experimental period but remained within the normal range in both the groups. The whole blood and plasma transfusion was found to upgrade the haematological and biochemical parameters in anaemic calves. The blood and plasma transfusion can be an effective tool for clinical management of anaemic calves. Vol. 9, No. 2, August 2022: 153-164